Model Sistem Pendukung Keputusan Orientasi Pasar: Studi Kasus Factory Outlet - Marwan Rajat (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
In a marketing development at the factory outlet needed an alternative to quick decisions and was followed by changes in the existing management. Although the reality on the ground that there is only a change in the marketing of factory outlet but not in management. The model helps decision support system to model changes in marketing and other business functions with information technology in responding to changing customer needs to factory outlets. To assist in this modeling is needed as data from the company's internal data, and customer data as external data. These data are quantitative data obtained from the performance appraisal is a comparison between perceive (the performance perceived by customers) with the expectation (customer expectations), then the results will be used to find correlations between the variables of market orientation with customer value. For the correlations obtained will be seen that the market orientation variables most influence on customer value to determine changes in activity on the existing business functions in the factory outlet with the help of COBIT model. The result of this decision support system model is an alternative decision to improvement in activity in the factory outlet business functions.